Klinik Pertanahan Sebagai Perwujudan Reforma Agraria Dan Sarana Penyelesaian Permasalahan Tanah Di Desa - Rohmat Junarto (LPPM Universitas HKBP Nommensen, 2023)
The presence of land and spatial issues in the Bejiharjo Urban Village presents a significant challenge in providing understanding and awareness to the community in its management. Transfer of knowledge to raise awareness among the people of Bejiharjo faces challenges such as strong institutional and political bureaucracy, geographical diversity of the region, and people's educational backgrounds. This paper presents the findings of a qualitative study, the data for which was gathered through the focus group discussion (FGD) method and interviews with 20 residents. Discussions focused on conveying the diversity of potential areas worth developing, while interviews were used to address land and spatial issues. The findings show that counseling about the diversity of regional potentials and providing solutions to land problems can be used to foster community empowerment, improve the quality of land services, and meet the community's security needs for their land. However, the uniformity of land service requirements, the ease of bureaucracy in each institution, and the political will of the authorities to assist residents in the regions are the keys to achieving social welfare.